5.-Max Z = 4X1 – 2X2 + 3X3
S.a. X1 – X2 – X3 ≤ 8
X2 – X3 ≤ 4
X1 + X3 ≤ 12
X1 , X2 , X3 ≥ 0
Forma Estandarizada :
Max Z = 4X1 – 2X2 + 3X3 + 0S1 + 0S2 + 0S3
X1 – X2 – X3 + S1 = 8
X2 - X3 + S2 = 4
X1 + X3 + S3 = 12
X1, X2, X3, S1, S2, S3 ≥ 0
| | CJ | 4 | -2 | 3 | 0 | 0 | 0 | |
CB | XB | bi | X1 | X2 | X3 | S1 | S2 | S3 | θK |
0 | S1 | 8 | 1 | -1 | -1 | 1 | 0 | 0 | 8 |
0 | S2 | 4 | 0 | 1 | -1 | 0 | 1 | 0 | - |
0 | S3 | 12 | 1 | 0 | 1 | 0 | 0 | 1 | 12 |
| ZJ | 0 | 0 | 0 | 0 | 0 | 0 | 0 | |
| ZJ + | CJ | -4 | 2 | -3 | 0 | 0 | 0 | |
4 | X1 | 8 | 1 | -1 | -1 | 1 | 0 | 0 | - |
0 | S2 | 4 | 0 | 1 | -1 | 0 | 1 | 0 | - |
0 | S3 | 4 | 0 | 1 | 2 | -1 | 0 | 1 | 2 |
| ZJ | 32 | 4 | -4 | -4 | 4 | 0 | 0 | |
| ZJ + | CJ | 0 | -2 | -7 | 4 | 0 | 0 | |
4 | X1 | 10 | 1 | -1/2 | 0 | 1/2 | 0 | 1/2 | |
0 | S2 | 6 | 0 | 3/2 | 0 | -1/2 | 1 | 1/2 | |
3 | X3 | 2 | 0 | 1/2 | 1 | -1/2 | 0 | 1/2 | |
| ZJ | 46 | 4 | -1/2 | 3 | 1/2 | 0 | 7/2 | |
| ZJ + | CJ | 0 | 3/2 | 0 | 1/2 | 0 | 7/2 | |
X1 = 10 X3 = 2 S2 = 6 Z = 46
Max Z = 4(10) - 2(0) + 3(2) + 0(S1) + 0(6) + 0(S3) = 46
Max Z = 46
6.-
Max Z = 3X1 – 2X2 + X3
S.a.
X1 – X2 - X3 ≤ 2
X1 – X3 ≤ 4
X1 + X3 ≤ 6
X1 , X2 , X3 ≥ 0
Forma Estandarizada :
Max Z = 3X1 – 2X2 + X3 + 0S1 + 0S2 + 0S3
X1 – X2 – X3 + S1 = 2
X1 - X3 + S2 = 4
X1 + X3 + S3 = 6
X1, X2, X3, S1, S2, S3 ≥ 0
| | CJ | 3 | -2 | 1 | 0 | 0 | 0 | |
CB | XB | bi | X1 | X2 | X3 | S1 | S2 | S3 | θK |
0 | S1 | 2 | 1 | -1 | -1 | 1 | 0 | 0 | 2 |
0 | S2 | 4 | 1 | 0 | -1 | 0 | 1 | 0 | 4 |
0 | S3 | 6 | 1 | 0 | 1 | 0 | 0 | 1 | 6 |
| ZJ | 0 | 0 | 0 | 0 | 0 | 0 | 0 | |
| ZJ + | CJ | -3 | 2 | -1 | 0 | 0 | 0 | |
3 | X1 | 2 | 1 | -1 | -1 | 1 | 0 | 0 | -2 |
0 | S2 | 2 | 0 | 1 | 0 | -1 | 1 | 0 | - |
0 | S3 | 4 | 0 | 1 | 2 | -1 | 0 | 1 | 2 |
| ZJ | 6 | 3 | -3 | -3 | 3 | 0 | 0 | |
| ZJ + | CJ | 0 | -1 | -4 | 3 | 0 | 0 | |
3 | X1 | 4 | 1 | -1/2 | 0 | 1/2 | 0 | 1/2 | |
0 | S2 | 2 | 0 | 1 | 0 | -1 | 1 | 0 | |
1 | X3 | 2 | 0 | 1/2 | 1 | -1/2 | 0 | 1/2 | |
| ZJ | 14 | 3 | -1 | 1 | 1 | 0 | 2 | |
| ZJ + | CJ | 0 | 1 | 0 | 1 | 0 | 2 | |
X1 = 4 X3 = 1 S2 = 2 Z = 14
Max Z = 3(4) - 2(0) + 1(2) + 0(S1) + 0(2) + 0(S3) = 14
Max Z = 14
7.-
Max Z = X1 – X2 + X3
S.a.
2X1 – X2 ≤ 4
X2 – X3 ≤ 6
X2 + X3 ≤ 8
X1 , X2 , X3 ≥ 0
Forma Estandarizada :
Max Z = X1 – X2 + X3 + 0S1 + 0S2 + 0S3
2X1 – X2 + S1 = 4
X2 - X3 + S2 = 6
X2 + X3 + S3 = 8
No hay comentarios:
Publicar un comentario